Phamacopuncture and Dermal Application of Sebalgukhwa-san: Effects on Hair Growth in a Mouse Model of Alopecia - Min Jung Ji; Seong Chul Lim; Jae Soo Kim; Hyun Jong Lee; Yun Kyu Lee (Journal of Acupuncture Research, 2019)
Background This study was conducted to evaluate the effects of pharmacopuncture and dermal application of Sebalgukhwa-san extracts on hair growth in an alopecia mouse model. Methods Twenty-one C57BL/6 mice were divided into 3 groups; control group-normal saline injection or vehicle solution application, positive control group-minoxidil (MNXD), experimental group-pharmacopuncture and applied Sebalgukhwa-san (SGS) extract. The effects of the treatment on hair growth, were determined through photographs, and phototrichogram analysis by folliscope. Hair follicle morphometry by hematoxylin-eosin staining was performed, and hair growth-related protein expression of vascular endothelial growth factor, insulin like growth factor-1, and transforming growth factor-beta 1 were monitored by Western blotting. Serum levels of aspartate aminotransferase and alanine aminotransferase were measured for liver function test. Results Body weight increased consistently in all groups. Hair growth was improved in the MNXD and SGS groups compared with the control. Hair density and thickness improved statistically significantly in the MNXD and SGS groups compared with the control p < 0.05. The number of hair follicles improved in the MNXD and SGS groups compared with the control but the size did not. The expression of vascular endothelial growth factor and insulin like growth factor-1 increased, and there was a decrease in the expression of transforming growth factor-beta 1 in the MNXD and SGS groups compared with the control, however, there was no significant difference. Sebalgukhwa-san treatment had no toxicity in liver function tests. Conclusions Pharmacopuncture and dermal application of Sebalgukhwa-san extract may be therapeutically beneficial for the treatment of alopecia.